Gambaran Budaya Keselamatan Pasien Oleh Perawat di Rumah Sakit : Studi Literatur - Dedi Iswari; Endang Pertiwiwati; Ichsan Rizany (Nerspedia, 2023)
Background: Health care hospitals whose environment is very dense with activities so that there is a risk of unwanted events(KTD) that have an impact on injury to death, in an effort to minimize adverse events related to patient safety aspects, hospital management must produce a patient safety culture that must be applied in all cases. hospital scope.